Catálogo de nuevas variedades de papa: sabores y colores para el gusto peruano. - De Haan, Stef; Janampa, Analí; Bastos Zuñiga, Carolina; Gastelo Benavides, Manuel Antonio; Hualla, Vilma; Zúñiga López, Luz Noemí; Cabrera Hoyos, Héctor Antonio; Torres Maita, Rafael Vinci; Morote Quispe, Máximo; Pacheco del Castillo, Miguel Ángel; Arcos Pineda, Jesús; Cahuana Quispe, Rodolfo; et al. (Instituto Nacional de Innovaciön Agraria - INIA Centro Internacional de la Papa - CIP, 2019)
92 paginas